Biocontrol potential of actinomycetes against Xanthomonas axonopodis pv. punicae, a causative agent for oily spot disease of pomegranate. Issue 3 (3rd March 2016) - Chavan, N. P.; Pandey, R.; Nawani, N.; Nanda, R. K.; Tandon, G. D.; Khetmalas, M. B.
ABSTRACT: India is a largest producer of pomegranate with high export value. The cultivation is affected with the oily spot disease caused by Xanthomonas axonopodis pv. punicae infection. The present study aims to control the disease with newer biocontrol methods. Thirty-six isolates of X. axonopodis were isolated from different varieties of infected pomegranates fruits from Maharashtra. Forty strains of actinomycete were also isolated from natural sources and screened for their antagonistic activity against X. axonopodis isolates. Eight strains of actinomycete were screened out for their high antagonistic activity and were optimized for maximizing antibiotic production. The extracted compound from A5 strain exhibited maximum inhibitory activity against all the pathogenic isolates with a MIC in the range of 0.625 to 1.25 mg mL −1 . It was identified as Streptomyces violaceusnige by 16SrRNA gene sequencing (Accession number KP208943). The extracted compound belonged to aminoglycosides with a molecular formula C22 H28 N3 O6 determined by thin layer chromatography, high-performance liquid chromatography, gas chromatography-mass spectroscopy, nuclear magnetic resonance spectroscopy, fourier transform infrared spectroscopy and carbon hydrogen nitrogen ratio analysis. In vivo biocontrol studies with strain A5 and its extracted compound effectively prevented the growth 36 Xanthomonas isolates inoculated on pomegranate fruits, illustrating its biocontrol potential against the oily spot disease of pomegranate.